The Effect of Career Development, Non-Financial Compensation, and Work Family Conflict On Employee Performance - Anik Herminingsih; Lusi Feronika Nainggolan (Green Publisher Indonesia, 2025)
This study examines the impact of career development, non-monetary benefits, and work-family conflict on employee performance at PT. Telkom Assurance Unit Central Jakarta Access. The participants in this research were workers employed at PT. Telkom Akses Jakarta Pusat. The subjects of this study consist of all employees at PT. Telkom Access Central Jakarta Assurance division has 178 staff members. The participants involved in this research consisted of 108 individuals. This research employed a random sampling method. The analysis of the data employed is statistical analysis utilizing SEM-PLS. The findings of this research suggest that career development positively and significantly impacts employee performance. Non-financial compensation has a positive and significant effect on employee performance and work family conflict has a positive and significant effect on employee performance.